Training future healthcare sustainability leaders: Lessons learned from a Canadian-wide medical student community of practice - Owen Dan Luo; Jacob Joel Kirsh Carson; Victoria Sanderson; Rosemarie Vincent (Elsevier, 2021)
Healthcare systems are significant contributors to the climate crisis and thus, healthcare must transform to reduce its emissions. However, future physicians are underprepared to lead initiatives to reduce healthcare emissions and to transition to low-carbon models of healthcare provision. Project Green Healthcare/Projet Vert la Santé (PGH/PVLS) is a community of practice of seven Canadian medical student teams leading sustainability-oriented projects in their local healthcare systems and medical schools. The nine month progress reports that participating teams submitted were analyzed to characterize network growth and impact, as well as to identify the facilitators of medical student-led healthcare sustainability projects and the learning outcomes of PGH/PVLS participants. In nine months, the PGH/PVLS network of medical students and their health sector collaborators grew 129%, from 45 to 103 individuals involved. Medical student teams described facilitators to their healthcare sustainability projects that were summarized into five themes: 1) working with motivated team members and healthcare sector allies, 2) establishing a successful team environment, 3) receiving support to navigate a complex healthcare system, 4) taking a structured quality improvement approach, and 5) being a part of a community of practice. Learning skills to become environmentally-conscious healthcare providers and appreciating the need for top-down systems-level advocacy were identified as key learning outcomes from the PGH/PVLS program. Developing communities of practice for medical students to engage in healthcare sustainability projects represents an opportunity to achieve net-zero healthcare by preparing future physicians to practice environmentally-conscious healthcare, and by empowering them to become healthcare sustainability leaders.